Pengaruh Pemberian Reward, Punishment dan Motivasi Kerja terhadap Kinerja Karyawan - Irwan Zulkifli; Rosalinda Rosalinda (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
This study aims to analyze the effect of reward, punishment and work motivation on employee performance at PT Garuda Verdana Kargo. The analysis technique uses multiple regression analysis with the least squares equation and tests the hypothesis using t-statistics and the F test to test the regression coefficients partially and simultaneously, test the validity, reliability, and test the classical assumptions. The results of the study show that there is an effect of reward on employee performance at PT. Garuda Verdana Cargo. There is an influence of Punishment on Employee Performance of PT. Garuda Verdana Cargo, together with Reward Punishment and Work Motivation have a significant influence on Employee Performance at PT. Garuda Verdana Cargo